2015
DOI: 10.3390/ijerph120606136
|View full text |Cite
|
Sign up to set email alerts
|

Does Treatment Impact Health Outcomes for Patients After Acute Coronary Syndrome?

Abstract: Background: Mortality rates for acute coronary syndrome (ACS) patients are still very high all over the world. Our study aimed to investigate the impact of ACS treatment on cardiovascular (CV) mortality eight years following ACS. Methods: A retrospective cohort study with a total of 613 patients was used. The data was collected from databases and medical records. An evidence-based treatment (EBT) algorithm was used based on the ESC guidelines. Logistic regression analysis and standardized odds ratios with 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Evaluation of AMPs at different stages showed a change at every stage. According to a study conducted by Umbrasiene et al , continuing the same treatment for a longer period of time can significantly improve CV mortality rates 10 . Although initial therapy stabilizes the patient's condition, relieves ischemic pain, and reduces the risk of myocardial damage to prevent further ischemia, 11 studies recommending the use of specific therapeutic agents are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of AMPs at different stages showed a change at every stage. According to a study conducted by Umbrasiene et al , continuing the same treatment for a longer period of time can significantly improve CV mortality rates 10 . Although initial therapy stabilizes the patient's condition, relieves ischemic pain, and reduces the risk of myocardial damage to prevent further ischemia, 11 studies recommending the use of specific therapeutic agents are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that the use of clopidogrel reduced CV mortality to a statistically significant ( p = 0.004) extent. The study further added that the use of evidence-based treatment algorithm is effective for the management of CV complications in patients with ACS to a significant extent ( p < 0.001) 10 . Ruff et al further elaborated that the time duration for which anticoagulant therapy is continued is extremely important and must be decided on careful assessment because of increased risk of bleeding events on long-term use 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The recommended medications include aspirin and antiplatelet, which prevent blood to clot; beta blocker and angiotensin co-enzyme inhibitor (ACEi)/angiotensin receptor blocker (ARB), which are blood pressure lowering medications; and statin/lipid lowering therapy, which are cholesterol lowering medications [ 8 , 9 ]. These evidence-based medications have been proven to reduce the risk of mortality and major adverse cardiovascular events, with further risk reduction when used in combination, and are recommended to be taken long-term [ 4 7 , 10 , 11 ]. However, studies suggest that there are social subgroups that receive optimal treatment less often [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%